Association of brain functional magnetic resonance activity with response to tumor necrosis factor inhibition in rheumatoid arthritis. Issue 2 (28th January 2013) - Rech, Juergen; Hess, Andreas; Finzel, Stephanie; Kreitz, Silke; Sergeeva, Marina; Englbrecht, Matthias; Doerfler, Arnd; Saake, Marc; Schett, Georg
Abstract: Objective: To test whether brain activity predicts the response to tumor necrosis factor inhibitors (TNFi) in patients with rheumatoid arthritis (RA). Since clinical and laboratory parameters have proven unsuccessful in predicting response, we followed a radically different concept, hypothesizing that response to TNFi depends on central nervous system activity rather than the clinical signs of disease. Methods: Sequential testing by functional magnetic resonance imaging (MRI) of the brain, anatomic MRI of the hand, and clinical assessment of arthritis were carried out in 10 patients with active RA before and 3, 7, and 28 days after the start of TNFi treatment. Results: Baseline demographic and disease‐specific parameters were identical in TNFi responders and nonresponders. The mean ± SEM decrease in the Disease Activity Score in 28 joints after 28 days was −1.8 ± 0.3 in TNFi responders (n = 5) and −0.2 ± 0.1 in nonresponders (n = 5). Responders showed significantly higher baseline activation in thalamic, limbic, and associative areas of the brain than nonresponders. Moreover, brain activity decreased within 3 days after TNFi exposure in the responders, preceding clinical responses (day 7) and responses observed on the anatomic hand MRI (day 28). Conclusion: These data suggest that response to TNFi depends on brain activity in RA patients, reflecting the subjective perception of disease.